1992
DOI: 10.1111/j.1476-5381.1992.tb12752.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase responsible for l‐arginine‐induced relaxation of rat aortic rings in vitro may be an inducible type

Abstract: 1 Characteristics of L-arginine-induced non-endothelial nitric oxide (NO) formation in rat isolated thoracic aorta were investigated. 2 Relaxation to L-arginine in arterial rings devoid of endothelium developed about 2 h after the first challenge with L-arginine and reached a maximum after a further 4 h of incubation. 3 After the arteries had relaxed in response to L-arginine, guanosine 3':5'-cyclic monophosphate (cyclic GMP) production was stimulated. In fresh arteries that had not yet relaxed in response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…This raises the prospects of the presence of more than one regulating mechanism. The significant reduction of intimal thickness and improvement of endothelial function observed with l-arginine treatment is in harmony with the report of Moritoki et al (31), who showed that l-arginine treatment causes relaxation of rat aortic rings.…”
Section: Aortic Intimal Thickness In Nitroglycerin-treated Rabbitsupporting
confidence: 78%
“…This raises the prospects of the presence of more than one regulating mechanism. The significant reduction of intimal thickness and improvement of endothelial function observed with l-arginine treatment is in harmony with the report of Moritoki et al (31), who showed that l-arginine treatment causes relaxation of rat aortic rings.…”
Section: Aortic Intimal Thickness In Nitroglycerin-treated Rabbitsupporting
confidence: 78%
“…Initial efforts to determine regional NO biosynthesis by determining tissue nitrite/nitrate and cGMP levels in slices of dissected renal zones, isolated glomeruli, and various cell cultures systems. These studies indicated that tissues of both the renal cortex and medulla were indeed capable of generating NO in abundant amounts (6,10,13,25,36,69,93,108).…”
Section: Localization Of No Production Within Vascular and Tubular Stmentioning
confidence: 97%
“…Angiograms were then obtained periodically (1, 2, 3, 4, 5, 6, 7 hours) after LPS solution (0.5 rag/2 ml saline) or saline was injected into the cistema magna through a 22 G spinal needle. In some experiments, L-arginine (100 gmol), N~-monomethyl-L-arginine (L-NMMA, 10 gmol), vasopressin (10 nmol) or bradykinin (10 nmol) in 2.0 ml of saline were injected by the same route 6 hours after LPS injection, when submaximal dilation of the basilar artery had been obtained, and angiography was then performed over the next hour (5,10,15,20,25,30,45, 60 rain).…”
Section: Angiographymentioning
confidence: 99%
“…The expanding family of nitric oxide synthase isoforms generally divide into two categories: constitutive forms regulated by Ca 2+ and calmodulin in vascular endothelium or neuronal cells, and cytokine-inducible forms, that are less sensitive to Ca 2 § but are induced in various cell types including vascular smooth muscle cells, macrophages, neutrophils, and liver cells, under pathological conditions [14,20].…”
Section: Introductionmentioning
confidence: 99%